Model Pengukuran Motivasi dan Minat Karir Mahasiswa Akuntansi Sebagai Konsultan Pajak: Studi pada Perguruan Swasta di Kota Medan - Novien Rialdy; Maya Sari; Mukmin Pohan (Politeknik Ganesha Medan, 2022)
This study aims to produce a Model of Measurement of Motivation and Career Interest of Accounting Students as Tax Consultants: Studies at Private Universities in Medan City. While the specific objective is to study the factors that influence the motivation and career interest of Accounting Students as Tax Consultants at Private Universities in Medan City and produce a Measurement Model of Motivation and Career Interests of Accounting Students as Tax Consultants: Studies at Private Universities in Medan City. The population in this study were all accounting students at several private universities in Medan City. Sampling in this study used purposive sampling with the criteria of students majoring in accounting in semester IV and VI. The type of data used in this research is primary data. Data were collected by distributing questionnaires to students. The data analysis technique used is descriptive statistical analysis and data analysis using the help of a computer program, namely SPSS (Statistical Package for Social Science). The results show that partially and simultaneously quality motivation, career motivation and economic motivation have a significant effect on Student Career Interests. Private University Accounting in Medan City.